Da usura ao desperdício : o tempo de um pecado - Pinto, Álvaro Rodrigues (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The economic development that takes place after the year 1000 entailed the creation, on the part of the emerging bourgeoisie, of a new concept of time, rational and urban, that was opposed to the biblical, theological and rural time, and was materialised, at the beginning of the 14th century, in the invention of the mechanical clocks. The clergy seek to be seen as associated to these machines of time and power, and end up adapting to this new time whose waste they will deem a sin.